The EIUS Unicompartmental Knee Design: Early Failure in Elderly Patients - Barnes, C. Lowry; Lincoln, Daniel; Wilson, Becky (The Journal of Knee Surgery, 2013)
This report presents the results of 34 unicompartmental knee replacements in 28 elderly patients. The mean age of patients at the time of index surgery was 78.7 years. All cases were performed by a single surgeon over a 16-month period. In all cases, the EIUS Unicompartmental Knee System (Stryker, Mahwah, NJ) was used. The surgeon was technically experienced at implanting EIUS knee prostheses prior to the start of this study.Knees were evaluated by Knee Society Score through 5 years, and patients were followed up by phone interviews for a minimum period of 8 years. With revision as the end point, the 5-year failure rate was 14.7% (n = 5), and the mean time to failure was 25.6 months (range: 4 to 44 months).At 8 years follow-up, 3 patients (4 knees) died for reasons unrelated to the knee implant, and 2 patients (4 knees) were lost to follow-up. Three knees in 3 patients were revised at 5.75 years, 7.0 years, and 8.0 years, respectively. The majority of knees that did not experience early failure remained pain and symptom free at minimum 8 years follow-up.We suspect the early failures were more likely due to a combination of the design characteristics and instrumentation of the EIUS prosthesis than surgical technique.
Keywords: unicompartmental knee arthroplasty; elderly; early failure; design